Kompetensi Technological Pedagogical And Content Knowledge Pada Mahasiswa Program Praktik Lapangan Program Studi Pendidikan Kimia Semester Ganjil Tahun Ajaran 2016/2017 - Rizki Wiguna; Zarlaida Fitri; . Erlidawati (Universitas Syiah Kuala, 2017)
AbstractTechnological Pedagogical and Content Knowledge (TPACK) is the insight to integrate technology into teaching in a particular material. Chemistry teachers are required to master the technology in teaching chemistry so that they become professional teachers. This study aims to determine the ability of TPACK towards the Internship student in delivering learning materials in the internship school. This research applied a descriptive study by using a quantitative approach. Samples of study are three students of Chemistry Education program taking internship program in SMAN 4 Banda Aceh (by being coded A1) and Syiah Kuala University High School Laboratory (by being coded B1 and B2). Data were collected by conducting through observation when internship students were in the classroom. Observations were carried out twice for each internship student. Observer in this study consisted of two people namely researchers and advisor of internship students. The results showed that mastery of learning material of internship students with A1, B1, and B2 code varied that the lowest score was 49% as sufficient category score and the highest score was 91% that was indicated as very good. The lowest score in the pedagogical knowledge of internship students was 54% as sufficient category while the highest score of 93% included as a very good category. The ability of technological knowledge reached at least 56%, as the highest category reached 81% that was categorized as very good. The ability of Content Knowledge for the lowest percentage was 50% as sufficient category, but the highest score was 80% as good category. The ability of technological pedagogical of internship students in lowest percentage was 52% categorized as sufficient category and the highest was 83% as very good. Pedagogical and content knowledge capability was attained in the lowest 58% as sufficient and the highest 97% as very good. The ability of technological pedagogical and content knowledge in the lowest was 47% categorized as sufficient category and the highest was 88% categorized as very good. On average ability of technological pedagogical and content knowledge of internship students were relatively good with the lowest scores on the technological content knowledge component of 63% and the highest for technological and pedagogical and content knowledge components were obtained about 72%.Keywords: Technological Pedagogical and Content Knowledge, Internship studentsAbstrakTechnological Pedagogical and Content Knowledge (TPACK) merupakan pengetahuan untuk mengintegrasikan teknologi ke dalam pengajaran materi tertentu. Guru kimia dituntut untuk menguasai teknologi dalam mengajarkan ilmu kimia sehingga menjadi guru yang profesional. Penelitian ini bertujuan untuk mengetahui kemampuan TPACK mahasiswa PPL dalam menyampaikan materi pembelajaran di sekolah latihan. Jenis penelitian ini adalah penelitian deskriptif yang menggunakan pendekatan kuantitatif. Sampel penelitian ini adalah 3 mahasiswa Program Studi Pendidikan Kimia yang mengikuti PPL di SMAN 4 Banda Aceh (selanjutnya diberi kode A1) dan SMA Laboratorium Unsyiah (selanjutnya diberi kode B1 dan B2). Data dikumpulkan dengan observasi ketika mahasiswa PPL mengajar dikelas. Observasi dilakukan sebanyak dua kali untuk tiap mahasiswa PPL. Observer dalam penelitian ini terdiri dari dua orang yaitu peneliti dan guru pamong mahasiswa. Hasil penelitian menunjukan bahwa pemahaman materi (CK) mahasiswa PPL dengan kode A1, B1, dan B2 bervariasi dengan skor terendah 49% termasuk kategori cukup dan tertinggi 91% termasuk kategori sangat baik. Skor terendah pada pengetahuan pedagogi (PK) mahasiswa PPL sebesar 54% termasuk kategori cukup sementara skor tertinggi mencapai 93% termasuk kategori sangat baik. Kemampuan pengetahuan teknologi (TK) paling rendah 56% dengan kategori cukup dan paling tinggi mencapai 81% dikategorikan sangat baik. Kemampuan pengetahuan TCK terendah adalah 50% dengan kategori cukup dan paling tinggi 80% termasuk kategori baik. Kemampuan TPK mahasiswa PPL paling rendah adalah 52% dikategorikan cukup dan paling tinggi 83% termasuk kategori sangat baik. Kemampuan PCK terendah adalah 58% termasuk kategori cukup dan tertinggi 97% termasuk kategori sangat baik. Kemampuan TPACK paling rendah adalah 47% dikategorikan cukup dan paling tinggi adalah 88% dikategorikan sangat baik. Rata-rata kemampuan TPACK mahasiswa PPL Program Studi Pendidikan kimia tergolong baik dengan skor paling rendah pada komponen TCK yakni 63% dan paling tinggi untuk komponen TK dan PCK sebesar 72%.Kata Kunci: Technological Pedagogical and Content Knowledge, mahasiswa PPL